Effects of drought stress on growth parameters, enzyme activities and proline content in chickpea genotypes (Bangladesh Journal of Botany, 2018)
Drought stress decreased leaf water absorption capacity and real water content and increase relative water content in genotypes of chickpea. It decreased chlorophyll a and b content. Drought increased peroxidase superoxide dismutase, glutathione reductase, ascorbate peroxidase and catalase in stress groups. Proline content increased drastically index stress condition.